GAMBARAN KESIAPSIAGAAN PADA SUATU RUMAH SAKIT DALAM PENANGGULANGAN BENCANA KEBAKARAN - Citra Aulia Amanda; Adriansyah Arya Pratama, Novita Sari, Abdurrozzaq Hasibuan (CV. ADIBA AISHA AMIRA, 2025)
The aim of this research is to obtain new information and new discoveries. Functions as proof or verification of existing information and as a determinant of hospital preparedness in dealing with fire disasters. This research was conducted as a literature review, with secondary data. The data collection method used in this research is the documentation method. The analytical method used involves analyzing the content of relevant research journals that meet certain criteria, which is then collected and summarized. There are 10 pieces of literature that discuss hospital preparedness in dealing with fire disasters, all of which are national journals that are searched on the Google Scholar portal using the keyword